Abortion: a look into the perspective of privacy rights and decision-making autonomy - Sobrado de Freitas, Riva; Almada Mozetic, Vinícius; Zilio, Daniela (Polski Przegląd Stosunków Międzynarodowych, 2018)
The study aims to investigate the right to privacy, decision-making autonomy and, profoundly, self-determination of the body as pro-abortion arguments. For that, an exploratory-explanatory, qualitative bibliographic research was carried out, using the deductive method. In relation to the results achieved, it is appreciated that, in fact, the arguments favorable to the practice deserve to be respected, since they are based on extremely important and solidly grounded rights. It follows, therefore, that there is extreme consistency in the justifications for abortion, and it must be taken into account, even though the arguments contrary to the practice deserve extreme respect.